Contemporary Girlhood and Anne Boleyn in Young Adult Fiction. Issue 1 (1st March 2020) - Russo, Stephanie
Abstract: Anne Boleyn has been narrativized in Young Adult (YA) historical fiction since the nineteenth century. Since the popular Showtime series The Tudors (2007–2010) aired, teenage girls have shown increased interest in the story of Anne Boleyn, Henry VIII's second and most infamous queen. This construction of Boleyn suggests that she was both celebrated and punished for her proto-feminist agency and forthright sexuality. A new subgenre of Boleyn historical fiction has also recently emerged—YA novels in which her story is rewritten as a contemporary high school drama. In this article, I consider several YA novels about Anne Boleyn in order to explore the relevance to contemporary teenage girls of a woman who lived and died 500 years ago.